Efficacy and Safety of Diclofenac–Hyaluronate Conjugate (Diclofenac Etalhyaluronate) for Knee Osteoarthritis: A Randomized Phase III Trial in Japan - Nishida, Yoshihiro; Kano, Kazuyuki; Nobuoka, Yuji; Seo, Takayuki (Arthritis & rheumatology (Hoboken, N.J.), 2021)
Objective To confirm the efficacy and safety of intraarticular (IA) injection of diclofenac covalently linked to hyaluronic acid (diclofenac etalhyaluronate [DF‐HA]; ONO‐5704/SI‐613) in patients with knee osteoarthritis (OA). Methods In a phase III multicenter, randomized, double‐blind, placebo‐controlled trial, eligible subjects ages 40–75 years with symptomatic knee OA (Kellgren/Lawrence score of 2 or 3) were randomly assigned to receive IA injections of DF‐HA 30 mg or placebo (citric acid–sodium citrate buffered solution; 1:1) once every 4 weeks for 20 weeks (a total of 6 injections). Subjects were followed up for 24 weeks. The primary end point was the mean change from baseline to 12 weeks in Western Ontario and McMaster Universities Osteoarthritis Index version 3.1 (WOMAC) pain subscale scores, measured on a 100‐mm visual analog scale. Safety was evaluated by adverse event monitoring. Results All 440 subjects received investigational products (220 received placebo and 220 received DF‐HA). The full analysis set and safety population comprised 438 subjects (220 in the placebo group and 218 in the DF‐HA group) and 440 subjects, respectively. At 12 weeks, subjects receiving DF‐HA showed significant improvement from baseline in the WOMAC pain subscale score (–23.2 mm) compared to subjects receiving placebo ( −17.1 mm), with a difference of −6.1 mm (95% confidence interval −9.4, −2.8; P < 0.001). The difference between groups was significant as early as week 1, and a difference was maintained for 24 weeks, although the difference at week 24 was not significant. Anaphylactic reactions were observed in 2 subjects receiving DF‐HA. Conclusion Our findings indicate that treatment with DF‐HA results in significant improvement in the WOMAC pain subscale score compared to placebo over 12 weeks. Anaphylactic reactions were observed, and further safety evaluation is needed.